Analysis Of The BPBD Website Of South Sumatra Province Using The Pieces Method - eka puji agustini (Universitas Mercu Buana Yogyakarta, 2026)
The rapid development of information technology has made it easier for people to access various information through the internet. Websites are one of the most effective media in disseminating information to the public. The Regional Disaster Management Agency (BPBD) of South Sumatra Province already has a website that provides various information related to disasters, organizational structure, public services, and publication of activities. However, since the beginning of its creation, the website has not been visited many times and has never been analyzed on its performance. This study aims to analyze the performance of the BPBD website of South Sumatra Province using the PIECES (Performance, Information, Economics, Control, Efficiency, and Service) method. The results of the analysis show that from the Performance aspect, the website obtained a grade C score on Google PageSpeed Insight and a grade D on Pingdom; the Information aspect shows a scale value of 3 (good); the Economics aspect is considered efficient due to low maintenance costs; the Control aspect obtained a grade C on the Sucuri Sitecheck and a grade D on the Observatory; the Efficiency aspect shows quite good results; while the Service aspect is considered quite good but still needs improvement in the presentation of information to the public. Overall, the South Sumatra Province BPBD website functions quite well but still needs optimization in its performance and service quality so that it can become a more effective disaster information medium.